Prosedur Pengembangan Dan Karakteristik Assesment Pembelajaran - Mumtahanah, Nurotun; Rahman, Tatang Aulia (Al Hikmah: Jurnal Studi Keislaman, 2018)
Abstract: In PP. No.19 of 2005, regarding national education standards, one of theeducational quality standards is the assessment standard. assessment is the process ofobtaining information in any form that can be used for the basis of making decisionsabout students both concerning the curriculum, learning programs, school climateand school policies. Permendikbud Number 66 of 2013, assessment of studentlearning outcomes at the level of primary and secondary education is based onprinciples that are objective, integrated, economical, transparent, accountable, andeducative. assessment in learning has a procedure, namely (a) describing basiccompetencies into indicators of learning achievement; (b) establish completenesscriteria for each indicator; (c) map competency standards, basic competencies,indicators, completeness criteria, and aspects contained in report cards; (d) mapcompetency standards, basic competencies, indicators, completeness criteria,assessment aspects, and assessment techniques; (e) establish assessment techniques byconsidering the characteristics of indicators. Characteristics of learning must meetseveral criteria, namely; reliable, valid, and useful about the performance of students,as well as fair. Keywords: Procedure, Characteristics, Learning Assessment